Do Gut Microbiomes Shift After Bariatric Surgery? A Literature Review - Zofia Sorysz; Piotr Kowalewski; Maciej Walędziak; Anna Różańska-Walędziak (Medicina)
The human gastrointestinal tract is estimated to be populated by 38 trillion bacteria from almost 1000 different species. The dominant phyla are Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria. However, the diversity and amount of gut microbiota depends on various factors. The importance of gut microbiota is increasingly noticed due to the influence of bacteria on energy homeostasis, the immune system, general health, and metabolism. Bariatric surgery is the mainstay treatment for patients with obesity. Two of the most common mechanisms are reducing gastric volume and decreasing ghrelin secretion. This literature review aims to depict the diverse impact of different bariatric procedures on gut microbiota. The original research papers were collected from the PubMed, Cochrane, and Elsevier databases. This literature review is focused on human studies. However, several references include animal models, specifically rats and germ-free mice. The findings suggest that bariatric surgery causes changes in the diversity of gut microbiota. However, the specificity of the changes depends on the type of bariatric surgery. The Firmicutes/Bacteroidetes ratio is elevated in the groups of patients with obesity compared to lean individuals. Bariatric surgery lowers the ratios impact on metabolism and energy absorption. Gut microbiota produces short-chain fatty acids, of which butyrate is responsible for strengthening the gut barrier, and acetate is correlated with fat deposition and lipogenesis. Moreover, changes in short-chain fatty acids influence insulin resistance and inflammation. In conclusion, bariatric surgery impacts gut microbiota, resulting in metabolic changes in patients, and the need for further study regarding long-term microbiota alterations post-operation is notable.